PENGARUH KOMPRES AIR HANGAT TERHADAP NYERI PADA PENDERITA FLEBITIS DI RS DKT JEMBER - Setiyowati, Dwi Rahayu; Handayani, Luh Titi; Putri, Fitriana (The Indonesian Journal of Health Science, 2017)
Pain is a complex sensation that can only be felt by those affected, a person's response to pain is different from one person to another. Phlebitis is an inflammation that occurs in veins that can cause redness, swelling and pain. One way to reduce pain is by applying warm compresses. The type of warm water compress that give the warm water compress it dry. In a dry warm water compresses can withstand temperatures longer than warm water compress wet, but  it  has  little  risk  of  making  sunburn.  The  purpose  of  this  study  is  to determine  the  effect  of  warm  water  compresses  to  pain  in  patients  with phlebitis  in RS DKT  Jember.  This  study is  a  pre-experimental design,  the design of one group pre-test post-test design. Samples in this study were 30 respondents using sampling techniques qouta. Collecting data using a scale VAS (Visual Analog Scale) and the questionnaire ID Pain. The results obtained showed that the measurement of pain in patients with phlebitis before being given a warm water compress Pain ID values obtained with the average value of 1.0333 and VAS pain scale (Visual Analog Scale) after being given a warm water compress on RS DKT Jember obtained average value 0.590 average. Statistical test results obtained by using the Wilcoxon test results obtained p value=0, 000, p<0.05, meaning there is an influence does warm water compresses to pain in patients with phlebitis in RS DKT Jember. This study was recommended to nursing personnel to use warm compresses as an alternative for reducing pain than using pharmacological therapy.Keywords: Dry Warm Water Compresses, Pain, Phlebitis.